TEACHING AIDS AND TEACHING MATERIALS FOR ELF CLASSES - Rustamova Gulbahor To'htasinovna (TADQIQOTLAR.UZ, 2024)
Annotation: As we know, teaching is an art, which includes knowledge, presentation, an art of dissemination. Teaching demands broad knowledge of subject matter in all horizons, complete curriculum with standards, positive and caring attitude with enthusiasm, and a desire for learning and techniques of classroom management and a desire to make a difference in the lives of young people. I am sure that nobody will deny the fact that a teacher is an aid and the activities used by the teachers are materials in the classroom.